Comparative Evaluation of Servers and Libraries for Web Mapping Applications - Γκούτα, Λυδία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2018)
With the advanced development of technology and the emergence of World Wide Web (WWW), the situation in Cartography changed. This was achieved with the development of Cartography in Internet interface (Web Μapping). In order to produce maps in such interfaces, and more specifically interactive maps, certain components are necessary, which consist the architecture of this system. On its simplest version, a database in which the data is stored as well as a GIS Server which will serve the data to the Internet is required. Through various web services the map can be published to internet provided that the symbolism has been applied properly and subsequently and on the client side now, the cartographic web application is taking place. This application is enriched with further operations such as the configuration of a friendly intercommunication environment, the interactive involvement of the user and the interactive attribution tools, like the zooming in/out, the panning etc. These last operations are accomplished by using web mapping library software such as the JavaScript libraries OpenLayers, Leaflet etc. Finally, for the structure of the presentation site the programming languages HTML, CSS and JavaScript are exploited. These tools combined are giving to the application its final form at a browser environment. In the present thesis the analysis and comparison of two of the most basic parts of this system is attempted. In chapter 2, the term web mapping is briefly analyzed as well as its architecture and its basic components. Subsequently (chapter 3), some of the most widely used web map servers for serving geospatial data through the internet are examined. Some of them are free and open-source, like GeoServer and MapServer and some are proprietary, namely the ESRI’s ArcGIS Server. Secondly (chapter 4), the most widely used JavaScript libraries for web map applications such as OpenLayers and Leaflet are also analyzed and compared. By publishing the web map on the internet each time by using a different map server and trying a different JavaScript library by creating a web map application for the Internet (chapter 5), useful and important results for the capabilities and offered operations of each server and library are derived. The advantages and disadvantages which accrued when publishing the map on the internet are analyzed as well as each one’s technical characteristics, the evaluation of the final product and the level of each one’s usability by using specific criteria (chapter 6). Lastly, in chapter 7, the conclusions of the comparison and evaluation of this web mapping software are presented.